2015
DOI: 10.5114/wo.2014.44121
|View full text |Cite
|
Sign up to set email alerts
|

Genistein-induced mir-23b expression inhibits the growth of breast cancer cells

Abstract: Aim of the studyGenistein, an isoflavonoid, plays roles in the inhibition of protein tyrosine kinase phosphorylation, induction of apoptosis, and cell differentiation in breast cancer. This study aims to induce cellular stress by exposing genistein to determine alterations of miRNA expression profiles in MCF-7 cells.Material and methodsXTT assay and trypan blue dye exclusion assays were performed to examine the cytotoxic effects of genistein treatment. Expressions of miRNAs were quantified using Real-Time Onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Analysis of miR‐23b by qPCR demonstrated that this miRNA is also downregulated. miR‐23b has been shown to be involved in a wide range of cellular processes and aberrant expression of miR‐23b has been reported in many types of cancers . Zhang et al showed that miR‐23b suppressed invasion and metastasis both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of miR‐23b by qPCR demonstrated that this miRNA is also downregulated. miR‐23b has been shown to be involved in a wide range of cellular processes and aberrant expression of miR‐23b has been reported in many types of cancers . Zhang et al showed that miR‐23b suppressed invasion and metastasis both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Genistein also induced miR-146a expression associated with suppression of pancreatic cancer cell invasion via downregulation of miR-146a targets such as EGFR, MTA-2, IRAK-1, and NF-κB [141] . More recently, genistein exhibited distinct cell growth inhibition of breast cancer cells (MCF-7) by up-regulation of miR-23b expression (56.69-fold compared with untreated cells) [142] .…”
Section: Dietary Compounds and Natural Products (Phenols And Terpenoimentioning
confidence: 99%
“…Notable are also its anti-tumor effects, demonstrated especially in breast cancer 20 , 36 38 and prostate cancer. 39 41 …”
Section: Discussionmentioning
confidence: 99%